Interaction of Remalan Brilliant Blue R dye with n-alkyltrimethylammonium chloride surfactants: conductometric and spectroscopic investigations - Ashraf El-Hashani; Manish Kumar Sah; Khaled Edbey; Rehab Gaber Ismael; Dileep Kumar; Ajaya Bhattarai (Royal Society Open Science)
Micellization behaviour, thermodynamics and dye–surfactant interactions are the main topics of this investigation into the relationship between Remalan Brilliant Blue R (RBBR) dye and n-alkyltrimethylammonium chloride (CnTAC; n = 12, 14, 16 and 18) surfactants. Conductometric analysis revealed that the critical micelle concentration decreased with increasing alkyl chain length, suggesting that longer chains formed better micelles. Due to electrostatic interactions, spectrophotometric analyses revealed notable alterations in RBBR absorption following contact with CnTAC. Benesi–Hildebrand and Scott equations were used to compute the binding constant (Kb), which increased with chain length, indicating stronger dye–micelle interactions. The spontaneous interactions between RBBR and micelles were confirmed by thermodynamic analysis, which showed negative Gibbs free energy values (ΔG). The stability of dye–micelle complexes is attributed to hydrophobic forces, as seen by the greater negative ΔG that was produced by longer alkyl chains. Interestingly, increased surfactant concentrations changed equilibrium and decreased dye adsorption by breaking up pre-formed RBBR–CnTAC complexes. These results highlight how important the length of the alkyl chain is for micelle formation, thermodynamic parameters and dye–surfactant interactions. As the length of the chain grew, the sequence of RBBR binding strength was found to be C12TAC < C14TAC < C16TAC < C18TAC.